Neutralization of SARS‐CoV‐2 requires antibodies against conformational receptor‐binding domain epitopes. Issue 1 (22nd September 2021) - Gattinger, Pia; Niespodziana, Katarzyna; Stiasny, Karin; Sahanic, Sabina; Tulaeva, Inna; Borochova, Kristina; Dorofeeva, Yulia; Schlederer, Thomas; Sonnweber, Thomas; Hofer, Gerhard; Kiss, Renata; Kratzer, Bernhard; et al.
Abstract: Background: The determinants of successful humoral immune response to the severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) are of critical importance for the design of effective vaccines and the evaluation of the degree of protective immunity conferred by exposure to the virus. As novel variants emerge, understanding their likelihood of suppression by population antibody repertoires has become increasingly important. Methods: In this study, we analyzed the SARS‐CoV‐2 polyclonal antibody response in a large population of clinically well‐characterized patients after mild and severe COVID‐19 using a panel of microarrayed structurally folded and unfolded SARS‐CoV‐2 proteins, as well as sequential peptides, spanning the surface spike protein (S) and the receptor‐binding domain (RBD) of the virus. Results: S‐ and RBD‐specific antibody responses were dominated by immunoglobulin G (IgG), mainly IgG1, and directed against structurally folded S and RBD and three distinct peptide epitopes in S2. The virus neutralization activity of patients´ sera was highly correlated with IgG antibodies specific for conformational but not sequential RBD epitopes and their ability to prevent RBD binding to its human receptor angiotensin‐converting enzyme 2 (ACE2). Twenty percent of patients selectively lacked RBD‐specific IgG. Only immunization with folded, but not with unfolded RBD, induced antibodies against conformational epitopes with high virus‐neutralizing activity. Conformational RBD epitopes required for protection do not seem to be altered in the currently emerging virus variants. Conclusion: These results are fundamental for estimating the protective activity of antibody responses after natural infection or vaccination and for the design of vaccines, which can induce high levels of SARS‐CoV‐2–neutralizing antibodies conferring sterilizing immunity. Abstract : IgG response in convalescent COVID‐19 patients is directed to folded but not to unfolded RBD or RBD peptides. IgGs to folded RBD are required for virus neutralization. Twenty percent of convalescent COVID‐19 patients selectively lack RBD‐specific IgG. Only immunization with folded, but not with unfolded RBD, induces antibodies with virus‐neutralizing activity. Abbreviations: COVID‐19, coronavirus disease 2019; IgG, immunoglobulin G; RBD, receptor‐binding domain; SARS‐CoV‐2, severe acute respiratory syndrome coronavirus 2.